Diagnosis of sport and leisure of the Rede Cedes/Acre: network methodological aspects of the study and construction processes of the Research Center (Revista de Estudios Brasileños, 2023)
This study aims to report the construction process and actions of the Acre’s Recreational and Leisure Sports Development Center, focusing on the description of the methodological aspects of the research titled “Diagnosis of sports and leisure in the state of Acre”. The Cedes Network enables the scientific initiation of academics and the qualification and training of young researchers, encourages academic production and holds scientific events, being an important center for the study of sports and leisure policies in the region. The diagnosis of sport and leisure was an investigation that involved 674 high school students on the campuses of the Federal Institute of Acre and the College of Application of Ufac. It stands out for its methodological rigor during planning, the process of preparing the research team, the construction and validation of the data collection instrument, the creation of the database, the analysis, presentation and interpretation of the results. The implantation of the Cedes Network in Acre is an achievement for the local community and the rich experiences resulting from the research planning and execution processes represented an important step towards the production of knowledge, useful for the debate and construction of public policies concerning sports and leisure.